American Protestantism in the age of psychology - Muravchik, Stephanie, 1970- (Cambridge University Press, 2011)
"The social history of three major psycho-spiritual movements since World War II shows that these groups innovated a practical religious psychology that nurtured participants' faith, fellowship, and responsibility"--Provided by publisher